2007
DOI: 10.1007/s10750-006-0503-7
|View full text |Cite
|
Sign up to set email alerts
|

Variations in kinetics of alkaline phosphatase in sediments of eutrophic, shallow, Chinese lakes

Abstract: Kinetics of alkaline phosphatase in sediments of a shallow Chinese freshwater lake (Lake Donghu) were investigated. Spatially, among 20 sites sampled, V max and K m values of alkaline phosphatase in surface sediments were higher in the zone adjacent to sites with the highest chlorophyll a concentrations. Vertically, there was a peak in V max at intermediate sediment depths in addition to the expected maximum at the surface. Some inhibitors, such as CuSO 4 , ZnSO 4 and Na 2 WO 4 , showed significantly different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The dissolved forms are usually characterized as dissolved inorganic phosphorus (DIP) and, more generally, soluble reactive phosphorus (SRP). Key steps (Malmaeus et al, 2006; Maurer and Boller, 1999; Nausch et al, 2004; Paytan and McLaughlin, 2007; Ruley and Rusch, 2004; Zhou et al, 2007) in phosphorus transformation are as follows:…”
Section: Case Study: Managing Phosphorus In Bahr El‐baqar Drainage Symentioning
confidence: 99%
“…The dissolved forms are usually characterized as dissolved inorganic phosphorus (DIP) and, more generally, soluble reactive phosphorus (SRP). Key steps (Malmaeus et al, 2006; Maurer and Boller, 1999; Nausch et al, 2004; Paytan and McLaughlin, 2007; Ruley and Rusch, 2004; Zhou et al, 2007) in phosphorus transformation are as follows:…”
Section: Case Study: Managing Phosphorus In Bahr El‐baqar Drainage Symentioning
confidence: 99%
“…The ability of the sediment to immobilize P increased further during the anthropogenic acidification era because of elevated terrestrial export of ionic aluminum (Al), suggesting that this P-immobilizing mechanism can occur in lakes with high Al inputs. Zhou et al (2007) investigated kinetics of alkaline phosphatase in sediments of a shallow Chinese freshwater lake (Lake Donghu), and they observed that the enzyme is immobilized in sediments, which became more stable with accelerated eutrophication. T he benthic nepheloid layer in Lake Biwa, Japan was studied by Kim et al (2007a), who found that potential activity of particlebound alkaline phosphatase was remarkably high in the nepheloid layer of a large mesotrophic lake during thermal stratification.…”
Section: Restoration and Treatmentmentioning
confidence: 99%